2001
DOI: 10.1002/1521-396x(200103)184:1<129::aid-pssa129>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Electrochromic Properties of Nanocrystalline WO3 Thin Films Prepared by Pulsed Excimer Laser Ablation Technique

Abstract: Tungsten oxide thin films with different stoichiometry have been deposited on In 2 O 3 : SnO 2 glass (ITO) and Si wafer by pulsed laser deposition (PLD) technique at different deposition temperatures and oxygen pressure. The structural properties of WO 3 thin films were analyzed by using a scanning accessory of transmission electron microscope (STEM), X-ray diffraction (XRD), Fourier transform infrared spectrum (FT-IR), Raman spectrum (RS). Thin films deposited at 200 C on ITO showed amorphous structure, those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The microstructure of WO 3 thin films investigated by SEM is illustrated in figure 4 (a) top view, and (b) cross section. The image of the surface shows very smooth without visible grains at 100 nm scale, in contrast with [10]. In the cross section, the material is very compact, without any cracks, or columnar shapes.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The microstructure of WO 3 thin films investigated by SEM is illustrated in figure 4 (a) top view, and (b) cross section. The image of the surface shows very smooth without visible grains at 100 nm scale, in contrast with [10]. In the cross section, the material is very compact, without any cracks, or columnar shapes.…”
Section: Resultsmentioning
confidence: 93%
“…In recent years significant effort has been devoted towards developing surface acoustic wave (SAW) sensors based on WO 3 sensing films, to be used for detection of gases like NO, H 2 S, NO 2 , SO 2 , CO, CO 2 . The WO 3 films have been deposited by various techniques as magnetron sputtering [1,2,3], electrochemical deposition [4,5], chemical vapor deposition [6,7], as well as laser ablation technique [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The films were deposited onto ITO coated glass and Si(111) substrates. Increasing oxygen background pressure during deposition was found to raise the resistance of the film; an atmosphere of 7 Pa of O 2 gave films that were conducting, 10 Pa semiconducting, and 15 Pa highly resistive [6].…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed laser deposition (PLD) is known to be an important method for the deposition of oxide materials [5], but there have been relatively fewer investigations of its utility in the deposition of WO 3 and substoichiometric WO x Following deposition using PLD from a WO 3 target using 308 nm radiation the microstructure and subsequent electrical properties of WO 3 thin films have been investigated [6,7], in particular the influence of substrate temperature and oxygen pressure. The films were deposited onto ITO coated glass and Si(111) substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In all the cases (polycrystalline or amorphous), however, the coloration efficiency is known to depend sensitively on the humidity content and the microstructure of the film. It has been shown that the porous and nanostructured WO 3 films with a high open surface have the potential to show an improved EC performance [5], [8]. A vast amount of work seen in the literature is directed towards the improvement of the EC performance of the WO 3 thin films through a careful tailoring of all the above said parameters.…”
Section: Introductionmentioning
confidence: 99%